Sirtuin 5 Deficiency Does Not Compromise Innate Immune Responses to Bacterial Infections - Heinonen, Tytti; Ciarlo, Eleonora; Théroude, Charlotte; Pelekanou, Aimilia; Herderschee, Jacobus; Le Roy, Didier; Roger, Thierry (Frontiers in Immunology, 2018)
Sirtuin 5 (SIRT5) is a member of the family of NAD+-dependent lysine/histone deacetylases. SIRT5 resides mainly in the mitochondria where it catalyses deacetylation, demalonylation, desuccinylation and deglutarylation of lysine to regulate metabolic and oxidative stress response pathways. Pharmacologic inhibitors of SIRT5 are under development for oncologic conditions, but nothing is known about the impact of SIRT5 on antimicrobial innate immune defenses. Using SIRT5 knockout mice, we show that SIRT5 deficiency does not affect immune cell development, cytokine production and proliferation by macrophages and splenocytes exposed to microbial and immunological stimuli. Moreover, preclinical models suggest that SIRT5 deficiency does not worsen endotoxemia, Klebsiella pneumoniae and Streptococcus pneumoniae pneumonia, Escherichia coli peritonitis, listeriosis and staphylococcal infection. Altogether, these data support the safety profile in terms of susceptibility to infections of SIRT5 inhibitors under development.